Optimism Bias and World Bank Project Performance. Issue 12 (2nd December 2022) - Ika, Lavagnon; Feeny, Simon
Abstract: This paper examines the correlates of optimism bias and its impact on World Bank project performance. We measure optimism bias in different ways using estimated Economic Rates of Return (ERR) of projects at approval and closure. We examine over 2, 800 World Bank projects that were appraised between 1960 and 2019. We find that approximately 60% of projects in the sample were prone to optimism bias. Correlates of optimism bias include both project and country characteristics. Findings also indicate that the incidence of optimism bias reduces the chance of a satisfactory project performance rate at the time of evaluation by 17–20%. Recommendations include embracing complexity and uncertainty in considering projects for approval, providing organizational incentives for ensuring projects are successful rather than ERRs being accurate, shifting some resources from appraisal to implementation, and changing the nature of project supervision.